2012
DOI: 10.1002/gcc.22013
|View full text |Cite
|
Sign up to set email alerts
|

Association between genomic alterations and metastatic behavior of colorectal cancer identified by array‐based comparative genomic hybridization

Abstract: Colorectal cancers (CRCs) exhibit multiple genetic alterations, including allelic imbalances (copy number alterations, CNAs) at various chromosomal loci. In addition to genetic aberrations, DNA methylation also plays important roles in the development of CRC. To better understand the clinical relevance of these genetic and epigenetic abnormalities in CRC, we performed an integrative analysis of copy number changes on a genome-wide scale and assessed mutations of TP53, KRAS, BRAF, and PIK3CA and DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
(79 reference statements)
3
17
0
2
Order By: Relevance
“…Fifty percent of the models (24/48 models) were KRAS mutant (75% of metastatic origin, 25% from primary tumors), 77% were TP53 mutant (37/48 models: 86% of metastatic origin, 14% from primary tumors), 17% were PIK3CA mutant (7/48 models: 87.5% of metastatic origin, 12.5% from primary tumors), and 8% were BRAF mutant (4/48 models: 50% of metastatic origin, 50% from primary tumors). These results are consistent with published reports comparing the genomic profiles of primary and mCRC tumors (40)(41)(42)(43). Previous and independent studies have demonstrated through use of a panel of tumor models established from cell lines that the status of KRAS, BRAF, PIK3CA, and PTEN did not significantly influence the response to aflibercept (44, data not shown).…”
Section: Genomic Characterization Of Pdx Modelssupporting
confidence: 91%
“…Fifty percent of the models (24/48 models) were KRAS mutant (75% of metastatic origin, 25% from primary tumors), 77% were TP53 mutant (37/48 models: 86% of metastatic origin, 14% from primary tumors), 17% were PIK3CA mutant (7/48 models: 87.5% of metastatic origin, 12.5% from primary tumors), and 8% were BRAF mutant (4/48 models: 50% of metastatic origin, 50% from primary tumors). These results are consistent with published reports comparing the genomic profiles of primary and mCRC tumors (40)(41)(42)(43). Previous and independent studies have demonstrated through use of a panel of tumor models established from cell lines that the status of KRAS, BRAF, PIK3CA, and PTEN did not significantly influence the response to aflibercept (44, data not shown).…”
Section: Genomic Characterization Of Pdx Modelssupporting
confidence: 91%
“…Another study demonstrated that CNVs were able to determine the lymph node metastasis in colorectal cancer (14). Evidence now indicates that the occurrence of CNVs in chromosome 4 may seriously induce lymph node metastasis in colorectal cancer (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies using cytogenetic analysis have found MSI cell lines and cancers to have a considerable presence of chromosomal aberrations, predominantly cnLOH events [27], [28], [29], [30]. Similarly, studies have reported the presence of CIN and CIMP to be inversely correlated [31], [32], and the incidence of frequent methylation to be associated with reduced rates and lengths of CNAs [33], [34], [35]. However, the majority of these studies did not stratify for presence of a BRAF mutation [31], [33], [35].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies have reported the presence of CIN and CIMP to be inversely correlated [31], [32], and the incidence of frequent methylation to be associated with reduced rates and lengths of CNAs [33], [34], [35]. However, the majority of these studies did not stratify for presence of a BRAF mutation [31], [33], [35].…”
Section: Introductionmentioning
confidence: 99%